Paradisrupt 4.0 : Managing supply chain 4.0 disruption systems - Gulam Muhammad, Nur; Fernando, Yudi (2021)
PARADISRUPT 4.0 is an alternative solution to assist the decision maker in the company to handle risk of Industry 4.0 disruption. PARADISRUPT 4.0 can assess in early stage of company issues related to as increasing the cost of Industrial 4.0 technology disruption and addressing material resources at the core of global value. Therefore, this PARADISRUPT 4.0 provides additional information to the manufacturing company to curb and overcome its Industry 4.0 readiness problems.